Contextual Factors Associated with Domestic Violence among Currently Married Women in Zambia: Findings from Zambia Demographic Health Survey - Thankian Kusanthan; Tamara Chansa-Kabali (Archives of Current Research International, 2017)
This study examined factors associated with domestic violence in the bid to offer a comprehensive understanding of the various factors associated with different types of domestic violence. The data for the study was derived from the Zambia Demographic Health Survey carried out by Central Statistical Office in 2013. The study was based on a sample of 9552 married women. Data was analyzed using Bivariate and Binary Logistic Regression. The results indicated that 30%, 23% and 16% of currently married women reported having experienced physical, emotional and sexual violence, respectively. The results of the logistic regression analysis shows that age, marital duration, place of residence, wealth status, educational level, partner drinking alcohol, having Sexually Transmitted Diseases (STDs) in the last 12 months and decision power as having significant influence on physical, emotional and sex violence among married women. Women’s decisions making power showed a strong likelihood of respondents reporting physical violence. Those who made decisions jointly were 1.3 times more likely to report having experienced physical violence as compared to those who made decisions alone. Women who were in marriage for 10-14 years were 1.3 times more likely to report sexual violence experience. Similarly, working women were 1.2 times more likely to report having experienced sexual violence at some point in their marriage in comparison to those who did not work. The findings of this study amplify the need to protect the women who are on the path to making positive contributions to both society and their families. This implies that stakeholders need to take note and address issues that determine and cause domestic violence which is an obstacle to women empowerment. Intervention programs that target men or both husband and wife are recommended.